Slip Effect on the Peristaltic Transport of MHD Fluid through a Porous Medium with Variable Viscosity - M. Abdulhadi, Ahmad; H. Al-hadad, Aya (Iraqi Journal of Science, 2023)
The present paper concerns with peristaltic analysis of MHD viscous fluid in a two dimensional channel with variable viscosity through a porous medium under the effect of slip condition. Along wave length and low Reynolds number assumption is used in the problem formulation. An analytic solution is presented for the case of hydrodynamic fluid while for magneto hydrodynamic fluid a series solution is obtained in the small power of viscosity parameter. The salient features of pumping and trapping phenomena are discussed in detail through a numerical integration. The features of the flow characteristics are analyzed by plotting graphs and discussed in detail. When .